Connectivity Continuous Improvement Program and Employee Performance - Wijayanti, Tri Cicik; Setini, Made; Darma, Dio Caisar; Purwadi, Purwadi; Alka, Prisciella Rizky (International Review of Management and Marketing, 2020)
In a turbulent business environment, company personnel are required to always make continuous improvements to the systems and processes used to generate value for customers and connect the performance of their employees. The purpose of the study was to analyze the extent of connectivity continuous improvement program and employee performance. The subjects of the study were employees of PT Kitadin Site Embalut located in Kutai Kartanegara Regency, East Kalimantan Province (Indonesia). Determination of the sample using probability sampling techniques totaling 60 employees and data processed through Multiple Linear Regression Analysis. The conclusions obtained based on field interviews is: employee development and training variables, improvement of work quality and productivity, and building cooperation between work teams has a significant effect on employee performance. Meanwhile, employee involvement in problem solving and good communication has no significant effect on employee performance. Employee involvement in organizational events is expected not only to the same person continuously, but in rotation. The things that need to be improved are that each employee must be able to openly communicate with fellow colleagues, as long as it is related to work related to the company. Keywords: Continuous improvement program, Employee performance, Indonesia. JEL Classifications: J24, L2 DOI: https://doi.org/10.32479/irmm.9161